A fuzzy DEMATEL method for analyzing key factors of the product promotion. (18th August 2018) - Gao, Su; Chen, Li-Shan; Chen, Pi-Lin
Abstract: Promotion, a means of encouraging consumers to purchase more products, is getting more and more attention. There is a large amount of literature discussing the issues regarding promotion and how important the key factors are. Most of the existing researches use the exact data to analyze problems, but there always exist various uncertainties in real-world problems. It is usually hard to define a traditional quantitative approach to solve these problems. Our research incorporates fuzzy concept into Decision Making Trial and Evaluation Laboratory (DEMATEL) method to identify the key factors affecting promotion and to analyze the pairwise relationships of these factors via the relevant mathematical models. According to the results of this study, we conclude that employing the proposed approach to identify key factors for promotion provides top managers with reference to draw up the marketing strategies.